1995
DOI: 10.1177/104063879500700314
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Indices in Healthy Foals from Birth to One Month of Age

Abstract: Hemostatic indices were determined in 45 healthy light breed foals, from birth to 1 month of age, and in 20 healthy adult (> 2 years of age) light breed horses. Blood samples were obtained from each foal at 4 ages: 1) < 24 hours, 2) 4-7 days, 3) 10-14 days, and 4) 25-30 days. The following hemostatic indices were determined: platelet count; prothrombin and activated partial thromboplastin times; activity concentrations of protein C, antithrombin III, plasminogen, alpha-2 antiplasmin, tissue plasminogen activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 17 publications
5
46
0
Order By: Relevance
“…1,17 The difference in fibrinogen values is likely due to different assay techniques. The 2nd limitation is the bias, which may have been introduced by grouping all samples together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,17 The difference in fibrinogen values is likely due to different assay techniques. The 2nd limitation is the bias, which may have been introduced by grouping all samples together.…”
Section: Discussionmentioning
confidence: 99%
“…1,17 Healthy foals have prolonged prothrombin time (PT) and activated partial thromboplastin time (aPTT), combined with decreased protein C, antithrombin activity (AT), and fibrinogen concentration compared with adults, similar to differences in coagulation between neonatal and adult human patients. 14,16,18 Foals with presumed septicemia have prolonged PT, aPTT, and increased concentration of FDPs with decreased AT and protein C concentration, but platelet and fibrinogen concentrations are not indicative of consumptive coagulopathy.…”
mentioning
confidence: 99%
“…Despite homeostatic mechanisms that function to maintain blood parameters within physiological levels, some changes are likely to occur [4]. In particular, it was demonstrated that hemostatic factors are reduced in several animals [2,5] including foals [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…For instance, in foals, low levels of coagulation factors and prolonged prothrombin (PT) and activated partial thromboplastin times (aPTT) are present at birth. 5 Knowledge of these differences is essential to the diagnosis of thrombotic and hemorrhagic problems of the neonate. However, defining normal values poses several difficulties, including age dependency, sample size and method of collection, and assay technique.…”
Section: ]/Dept-list)>mentioning
confidence: 99%
“…However, defining normal values poses several difficulties, including age dependency, sample size and method of collection, and assay technique. 5 Newborn animals are subjected to a number of different stimuli that could possibly lead to activation of the hemostatic system: stress with adrenergic stimulation, acidosis, hypoxia, thermal changes, and possibly, tissue factors liberated during the process of birth and placental separation. 24 Many studies have been carried out on the development of the coagulation system in lambs, 3,16,18 but little is known about kids.…”
Section: ]/Dept-list)>mentioning
confidence: 99%